Cholesterol-dependent transcriptome remodeling reveals new insight into the contribution of cholesterol to Mycobacterium tuberculosis pathogenesis - Jakub Pawełczyk (Nature Portfolio, 2021)
Abstract Mycobacterium tuberculosis (Mtb) is an obligate human pathogen that can adapt to the various nutrients available during its life cycle. However, in the nutritionally stringent environment of the macrophage phagolysosome, Mtb relies mainly on cholesterol. In previous studies, we demonstrated that Mtb can accumulate and utilize cholesterol as the sole carbon source. However, a growing body of evidence suggests that a lipid-rich environment may have a much broader impact on the pathogenesis of Mtb infection than previously thought. Therefore, we applied high-resolution transcriptome profiling and the construction of various mutants to explore in detail the global effect of cholesterol on the tubercle bacillus metabolism. The results allow re-establishing the complete list of genes potentially involved in cholesterol breakdown. Moreover, we identified the modulatory effect of vitamin B12 on Mtb transcriptome and the novel function of cobalamin in cholesterol metabolite dissipation which explains the probable role of B12 in Mtb virulence. Finally, we demonstrate that a key role of cholesterol in mycobacterial metabolism is not only providing carbon and energy but involves also a transcriptome remodeling program that helps in developing tolerance to the unfavorable host cell environment far before specific stress-inducing phagosomal signals occur.